2022
DOI: 10.1007/s11136-022-03154-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessing chemotherapy-induced peripheral neuropathy with patient reported outcome measures: a systematic review of measurement properties and considerations for future use

Abstract: Purpose Chemotherapy-induced peripheral neuropathy (CIPN) is a common toxicity of cancer treatment, with potential to significantly impact cancer survivors’ long-term quality of life. Patient reported outcome measures (PROMs) are increasingly utilised to evaluate CIPN. However, guidance remains lacking on how to identify fit for purpose PROMs with considerations necessarily differing when used in various research and in-clinic contexts. This study aimed to evaluate evidence about CIPN PROMs measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 75 publications
1
20
0
Order By: Relevance
“…The most commonly used PROMs (patient-reported outcome measures) to identify CIPN are the QLQ-CIPN20 and the FACT/GOG-Ntx questionnaire [ 14 , 15 ]. Among other things, they ask about the symptoms of the last 7 days, while, in our case, in addition to the current complaints, the onset of symptoms (and their presentation) was asked separately.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most commonly used PROMs (patient-reported outcome measures) to identify CIPN are the QLQ-CIPN20 and the FACT/GOG-Ntx questionnaire [ 14 , 15 ]. Among other things, they ask about the symptoms of the last 7 days, while, in our case, in addition to the current complaints, the onset of symptoms (and their presentation) was asked separately.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the two already established PROMs, our questionnaire asked about the localization of the complaints not only in the hands and feet, but in the entire body. We also asked in more detail about the respective impact on the daily lives of those affected [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, MIDs were estimated separately for the sensory and motor subscales of the QLQ-CIPN20. 16 However, due to a lack of demonstrated structural validity for these QLQ-CIPN20 subscales, 9 it has been recommended that the PROM be used in its entirety, rather than individual subscales. 40…”
Section: Comparison With Previous Mids Studiesmentioning
confidence: 99%
“…5 Previously demonstrated discordance between patient-and clinicianreported CIPN 6 suggests that PROMs may depict a broader spectrum of CIPN severity than clinician-based assessments, 7 enabling better understanding of symptom manifestation and effects on function. 8 A number of PROMs have been developed to assess CIPN 9 ; the 2 most commonly used and extensively validated are the EORTC Quality of Life -Chemotherapy-Induced Peripheral Neuropathy questionnaire (QLQ-CIPN20) 10 and the Functional Assessment of Cancer Therapy/ Gynecologic Oncology Group -Neurotoxicity questionnaire (FACT/GOG-NTX). 11 Previous studies have demonstrated that both PROMs are responsive in identifying change in CIPN symptoms over time.…”
Section: Introductionmentioning
confidence: 99%
“…While there remains no gold-standard clinical outcome measures for CIPN [ 9 ], there are a range of validated methods examining large fibre dysfunction in CIPN, including neurophysiological assessments, clinical examination [ 10 ] and patient-reported outcome measures [ 11 ]. However, there is a lack of validated tools to measure small nerve fibre damage or autonomic neuropathy in CIPN [ 12 ].…”
Section: Introductionmentioning
confidence: 99%